1975
DOI: 10.1128/jb.124.1.1-6.1975
|View full text |Cite
|
Sign up to set email alerts
|

Mu-induced polarity in the Escherichia coli K-12 ent gene cluster: evidence for a gene (entG) involved in the biosynthesis of enterochelin

Abstract: A strain of Escherichia coli K-12 has been isolated that carries a Mu bacteriophage-induced mutation in the ent gene cluster. Nutritional tests together with examination of the compounds accumulated by the mutant strain indicated that the mutant was blocked both in the synthesis of 2,3-dihydroxybenzoate and its subsequent conversion into enterochelin. Enzymic complementation assays of the mutant with several mutants each affected in one of the ent genes showed that the Mu-induced mutant was entA-, entBf, entC+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

1976
1976
1997
1997

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 25 publications
(29 reference statements)
0
8
0
Order By: Relevance
“…A further mutation in enterobactin biosynthesis, entG, was identified with use of bacteriophage Mu-induced mutagenesis and postulated to affect the conversion of 2,3-dihydroxybenzoate to enterobactin. 87 The significance of the entG mutation will be discussed in section III.D.…”
Section: Mechanistic Studies In the Biosynthesis Of Enterobactln A In...mentioning
confidence: 99%
“…A further mutation in enterobactin biosynthesis, entG, was identified with use of bacteriophage Mu-induced mutagenesis and postulated to affect the conversion of 2,3-dihydroxybenzoate to enterobactin. 87 The significance of the entG mutation will be discussed in section III.D.…”
Section: Mechanistic Studies In the Biosynthesis Of Enterobactln A In...mentioning
confidence: 99%
“…EntB/G and EntD are essential but their roles have not been determined. Ent B/G (32·5 kDa) seems to be a bifunctional protein (Staab & Earhart, 1990) required both for an early step in Ent biosynthesis (EntB activity; Rusnak et al, 1990) and an unidentified later step (EntG activity) (Greenwood & Luke, 1976, 1980; Woodrow et al, 1975); the early and late synthetic activities of Ent B/G are separable by mutation and appear to reside in the N- and C-termini of the protein, respectively. That EntB and EntG activities are on the same polypeptide is supported by the detection (unpublished results) of homology between the C-terminus of EntB/G and the N-terminus of iron-regulated HMWP2 of Yersinia enterocolitica (Guilvout et al, 1993); the homologous regions include a consensus substrate amino acid binding site for enzymes engaged in non-ribosomal peptide synthesis (Schlumbohm et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…From a common intermediate of aromatic amino acid synthesis, the enterobactin biosynthesis genes entC, entB, and entA convert chorismate to 2,3-hihydroxybenzoic acid (32). 2,3-Dihydroxybenzoic acid and Lserine are substrates for the production of enterobactin by enterobactin synthetase, which is composed of four enzymes, the products of entD, entE, entF, and entG (20,29). Release of the siderophore into the medium occurs by an uncharacterized mechanism.…”
mentioning
confidence: 99%
“…Laird et al (16) observed that the enterobactin cistrons span approximately 29 kilobases of DNA and are organized in the following order: entD, fes, entF, fep, and ent(CA)GBE. Thefep mutations used in this study all fell into the same complementation group now defined as fepB (21).…”
mentioning
confidence: 99%